Exploring family emotions in do-not-resuscitate (DNR) decision-making for hospitalized patients: A systematic review - Nur Aima Siagian; Yossie Susanti Eka Putri; Novy Helena Catharina Daulima; Yudi Ariesta Chandra; Ria Utami Panjaitan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: End-of-life decision-making, particularly Do-Not-Resuscitate (DNR) decisions for critically ill patients in hospital care, is an extremely difficult and often traumatic issue. This process has a profound impact on the mental health of families, causing anxiety, depression, stress, and even post-traumatic stress disorder (PTSD). There is currently little literature that thoroughly explores the diverse and profound emotional landscape, such as fear, optimism, well-being, and challenges experienced by families during the DNR decision-making process. Purpose: To examine the various emotions experienced by family members during the DNR decision-making process for patients hospitalised in hospital. Understanding these emotional experiences is crucial for improving support interventions, reducing conflict, and avoiding adverse psychological effects on families and healthcare providers. Method: A systematic review (SR) design was used in this study to evaluate and synthesise existing qualitative evidence on the emotional experiences of families. This design was chosen because it provides a better understanding of the family situation. To ensure its relevance to current clinical practice, this review used the PRISMA guidelines and the PICO framework. The publications included were published between 2020 and 2025 and were retrieved from electronic databases such as PubMed, SAGE, and Clinicalkey Nursing. Nine studies in the qualitative synthesis included 28 primary studies that were evaluated, most of which were qualitative or used mixed methods, conducted in several countries (such as the US, Australia, Taiwan, and Chile). The focus of the analysis was to find patterns, similarities, and differences in emotional experiences. Results: Families' experiences with DNR decisions are characterised by significant psychological stress. When families are faced with discussions about Goals of Care (GoC), they often feel unprepared, confused, and shocked. This situation is often exacerbated by time pressure. Families experience the deepest emotions, namely guilt and fear of making the wrong decision, with the family's main goal being to ‘do everything right so there are no regrets’. Conclusion: The DNR process is complex, dynamic, and emotional. This study shows that healthcare professionals must not only provide medical information but also acknowledge, validate, and assist families in coping with their emotional issues. To improve the quality of end-of-life care, clinical practice must shift to a more family-centred and friendly communication model that explicitly addresses the complex emotional dynamics that families face during difficult times in their lives.